2017
DOI: 10.1016/j.ruje.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Multinational companies from transition economies and their outward foreign direct investment

Abstract: Multinational companies (MNCs) based in 26 post-communist transition economies (PTEs) emerged during the 1990s. Their outward foreign direct investment (OFDI) boomed dramatically from 2000 to 2007 in these countries, and then muddled through ence is revealed in a sample of 15 PTEs for which data are available from 2000 to 2015. Most of these economies appear to be on the brink of moving from the second to the third stage of Dunning's investment development path. The geographical distribution of their OFDI favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
(6 reference statements)
0
12
0
4
Order By: Relevance
“…The pathways for these impacts of OFDI are that OFDI improves the per capita water footprint and the water footprint land density through (1) an economic scale effect, (2) an export growth effect, (3) domestic investment effect, and (4) consumption effect. It reduces the water footprint intensity through (5) a technological progress effect, (6) a factor allocation effect, (7) an industrial structural effect, and (8) an income effect. It increases the water footprint abandonment rate through (9) the environmental pollution effect and (4) the consumption effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathways for these impacts of OFDI are that OFDI improves the per capita water footprint and the water footprint land density through (1) an economic scale effect, (2) an export growth effect, (3) domestic investment effect, and (4) consumption effect. It reduces the water footprint intensity through (5) a technological progress effect, (6) a factor allocation effect, (7) an industrial structural effect, and (8) an income effect. It increases the water footprint abandonment rate through (9) the environmental pollution effect and (4) the consumption effect.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have generally found that the technological progress effects of OFDI are heterogeneous across different regions, different industries, and enterprises with different ownership characteristics. As for the industrial structure effect of OFDI, most studies have found that OFDI has played an optimizing role in the home country's industrial structure (Pan and Yuan, 2016, Andreff, 2017, Nie, 2017, Zhao and Ye, 2018) [6][7][8][9]. However, there is no clear consensus regarding the industrial structural effect of OFDI.…”
Section: The Impact Of Ofdi (None Analyzing the Impact Of Ofdi On Thementioning
confidence: 99%
“…(2) In terms of economic development, most scholars have refined their research objectives to focus on the factors of production. There are significant impacts of OFDI on the labour force [24], technological innovation [25], and energy consumption. Meanwhile, the impact of factor distortions on OFDI is also of great concern [26].…”
Section: Factors Influencing Ofdimentioning
confidence: 99%
“…This change is intended to bring greater benefits from supported foreign investment, which will increase the competitiveness of regions. Andreff (2017) proves that the promotion of science and research as well as the development of high-tech industries led to a decline in FDI outflow. For this reason, public policy was to support R&D and hightech sectors, for example, by amending the setting of investment incentives at a national and regional level in the priorities of regional innovation strategies.…”
Section: Discussionmentioning
confidence: 99%